History written with songs: The uprising songs in the archives of Adolf Dygacz - Krajewska, Agata (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
Digitization of nearly all songs from the archives of Adolf Dygacz is being realized in multiple stages. Presently, in 2021, it has gained special significance seeing as this year is the 100th anniversary of the Silesian Uprising. Songs about the uprisings constitute a notable part of his music collection. This article will analyze those particular type of songs collected by Adolf Dygacz which have not yet been published despite their undisputed value. Constituting witness accounts of people who experienced these events in person, they represent a local, bottom-up view of the history of the uprising, its reality, attitudes, and emotions. Therefore, this archive should never be dismissed or ignored.